ANALISIS KETIMPANGAN PEMBANGUNAN WILAYAH PESISIR DAN DARATAN TINGGI DI KABUPATEN PESISIR SELATAN: SYSTEMATIC LITERATURE REVIEW - Maijem Simponi; Efendi Efendi; Sefrinal Sefrinal; Okviani Syafti; Ramadhani Ramadhani (STKIP Pesisir Selatan, 2026)
This study aims to analyze the factors influencing development disparities, identify patterns of disparity between coastal and highland regions, and formulate strategies for sustainable regional planning based on a literature review. The method used is a Systematic Literature Review (SLR) following the PRISMA guidelines. Data were obtained from Google Scholar and Garuda through a selection process of 12 relevant scientific articles. The analysis was conducted using a thematic synthesis approach to identify the main themes of each study. The study’s findings indicate that development disparities are influenced by five main factors: infrastructure quality, regional accessibility, investment distribution, geographic conditions, and governance and human resources. Coastal regions tend to be more developed due to economic activities such as fishing and trade, while highland regions still face limitations in infrastructure and accessibility. Therefore, the novelty of this analysis lies in strategies that include improving interregional connectivity, ensuring equitable infrastructure distribution, developing local economic potential, and implementing development policies tailored to regional characteristics.